(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Robotics is a branch of engineering that combines more than one area of research and is used to design machines that helps us to assist in our day- to-day life. There are various inventions existing that are created using robotics and lawn mower is one such inventions. Lawn Mower or lawn cutter is a mechanical device whose work is to cut grass in our lawns. The automated lawn mower is used to do the same task automatically with help of different sensors and electrical components. This review aims to evaluate the technology that has been not used still to make the system more advanced. This paper presents the currently based system and techniques and retouches the areas that need to be modified for better performance.